2017
DOI: 10.1002/anie.201709844
|View full text |Cite
|
Sign up to set email alerts
|

Double Catalytic Kinetic Resolution (DoCKR) of Acyclic anti‐1,3‐Diols: The Additive Horeau Amplification

Abstract: The concept of a synergistic double catalytic kinetic resolution (DoCKR) as described in this article was successfully applied to racemic acyclic anti‐1,3‐diols, a common motif in natural products. This process takes advantage of an additive Horeau amplification involving two successive enantioselective organocatalytic acylation reactions, and leads to diesters and recovered diols with high enantiopurities. It was first developed with C2‐symmetrical diols and then further extended to non‐C2‐symmetrical anti di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…Among the several promising examples, benzothiazolopyrimidine, better known as homobenzotetramisole (HBTM), has assumed a leading position as a chiral catalyst. Chiral HBTMs have been successfully used in a number of asymmetric transformations1 a including the kinetic resolution of secondary alcohols and carboxylic acids,2 desymmetrization,3 acyl transfer,4 annulation processes,5 and lactonisation,6 among others 7. Nevertheless, despite the interest in optically active HBTMs,1 a there have been only limited reports on their enantioselective synthesis 8.…”
Section: Introductionmentioning
confidence: 99%
“…Among the several promising examples, benzothiazolopyrimidine, better known as homobenzotetramisole (HBTM), has assumed a leading position as a chiral catalyst. Chiral HBTMs have been successfully used in a number of asymmetric transformations1 a including the kinetic resolution of secondary alcohols and carboxylic acids,2 desymmetrization,3 acyl transfer,4 annulation processes,5 and lactonisation,6 among others 7. Nevertheless, despite the interest in optically active HBTMs,1 a there have been only limited reports on their enantioselective synthesis 8.…”
Section: Introductionmentioning
confidence: 99%
“…Its s value (27 for 1t)w as quite similar to the unsaturated precursor 1o(s = 29). [18] This hiddensymmetry strategy [19] represents the shortest synthesis of this target reported to date. We decided to apply this methodology to the total synthesis of (+ +)-cryptocaryalactone, [15] anatural germination inhibitor (Scheme 5).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…4 A representative example of this powerful amplification process is the acylative double catalytic kinetic resolution (DoCKR) of C2-symmetric (±)-1,2-syn and (±)-1,3-anti-diols ( Figure 1). [5][6][7][8] Due to the bis-alcohol functionality within the substrates, two KR processes can be in operation and are represented by the rate constants k1 and k2 for the first KR, and k3 and k4 for the second KR. If k1 > k2 and k3 > k4, the enantiomer of monoester preferentially generated in the 1 st KR is also preferentially acylated in the 2 nd KR (so called additive Horeau amplification).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only work from our research groups has demonstrated this concept, through the use of isothiourea catalysis in the sequential KR of (±)-1,3-anti and (±)-1,2-syn diols (Scheme 1). 7,8 The sequential KR of (±)-1,3-anti-diol 2a was achieved using (2R,3S)-HyperBTM 1 as catalyst (1 mol%) and propionic anhydride as acylating agent (1.05 equiv. ), to give (R,R)-diol 2a (41% yield, >99:1 er), (R,R)-monoester 3a (7% yield, 66:34 er) and (S,S)-diester 4a (41% yield, 98:2 er).…”
Section: Introductionmentioning
confidence: 99%